Webgos E-Module Development for Elementary Descriptive Writing Learning Outcomes: Pengembangan E-Module Webgos untuk Pembelajaran Menulis Deskripsi Sekolah Dasar - Ramadhani, Fitri; Syukri Syamsuri, Andi; Ratnawati, Ratnawati (Pedagogia : Jurnal Pendidikan, 2026)
General Background: Writing is a fundamental language skill in elementary education that supports communication competence and literacy development. Specific Background: However, many elementary students experience difficulties in descriptive writing, particularly in generating ideas, organizing sentences, and using appropriate vocabulary, while learning materials remain dominated by conventional printed modules. Knowledge Gap: Previous studies on Google Sites learning media have rarely developed structured e-modules specifically designed to guide descriptive writing learning processes. Aims: This study aims to develop a Webgos (Web Google Sites)–based e-module and evaluate its validity, practicality, and effectiveness for fifth-grade elementary students. Results: Using the ADDIE research and development model, the developed e-module obtained high validity scores from media and material experts (87%–97%), demonstrated high practicality based on learning implementation observations (98%) and positive teacher and student responses, and showed improved learning outcomes with average scores increasing from 45 in the pretest to 88 in the posttest with an N-Gain value of 0.79 in the high category. Novelty: The study presents an integrated Webgos e-module combining Google Sites structure, Canva-based materials, and interactive evaluation in a single digital learning system. Implications: The findings indicate that Webgos-based e-modules provide a feasible digital learning medium to support descriptive writing instruction in elementary education. Highlights • Web-based digital module designed through systematic ADDIE development stages• Expert validation confirmed high feasibility of the developed learning media• Student achievement scores increased substantially after module implementation Keywords Webgos E-Module; Google Sites Learning Media; Descriptive Writing Skills; Elementary School Students; ADDIE Development Model